RP-HPLC METHOD DEVELOPMENT AND VALIDATION OF MONTELUKAST SODIUM IN BULK DRUG AND DOSAGE FORM - SACHIN GHOLVE; SANJAY THONTE; OMPRAKASH BHUSNURE (International Journal of Pharma and Bio Sciences, 2015)
A reversed–phase high-performance liquid chromatography method is developed and validated for the determination of Montelukast Sodium (Montelukast) in bulk drug and pharmaceutical dosage form. The chromatographic determination was performed on Agilent 1220 Infinity LC with EZ chrome elite software with variable wavelength detector. The separation was conducted by using Zobrax Eclipse XDB-C18 column (4.6×150×5µm) with mobile phase consisting Methanol:Acetonitrile:Water (60:30:10). The mobile phase was delivered at the flow rate of 1.0 ml/min. The eluent was monitored at wavelength 344 nm and found a sharp and symmetrical peak with retention time 3.582. The method was validated for linearity, accuracy, precision, system suitability, and stability. The method was found to be linear over the concentration range 5-30µg/ml with coefficient R2 - 0.999. The developed HPLC technique is precise, specific, accurate and stable. Statistical analysis proves that the method is reproducible, selective and suitable to be applied for analysis of montelukast sodium in commercial pharmaceutical dosage form for routine quality control application.